ANALISA ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP KUALITAS TIDUR PASIEN CHRONIC KIDNEY DISEASE (CKD) ON HEMODIALISA (HD) DI RS BHAYANGKARA TK. I RADEN SAID SUKANTO - Indah Fitri Amelia (2022)
Kidneys are a very important part of the body that cannot be activated by other organs. Kidneys have a function, namely as a blood filter from metabolic waste. Signs and symptoms of disease arising from kidney disease can be found in other people such as physical or psychological symptoms. Hemodialysis (HD) is a process that occurs because the blood uses the blood system from the body outside the dialysis machine. Sleep disturbances will also have an impact on the patient's physical and mental health and can lead to a decrease in the patient's appearance such as cognitive and memory dysfunction, irritability, decreased alertness and concentration. Sleep pattern problems are one of the most common complaints in hemodialysis patients, several studies have shown that 50%-60% of patients with end-stage kidney disease do not have sleep problems. Complementary non-pharmacological therapy that can be implemented by nurses for patients with sleep disorders is EFT (Emotional Freedom Technique) therapy. This therapy is a therapy that combines the body's energy system and spirituality therapy by using the tapping method at certain points on the body. Measurement of sleep quality using the PSQI questionnaire. From the results of the intervention, it was found that the quality of the patient before the innovation intervention was 8 with a bad interpretation and after the intervention there was an increase in the quality of the patient's sleep with a result score of 4.